Financial Integration And International Asset Pricing Of Asean-5 Stock Markets: The Pricing Of Global, Regional And Currency Risk - Janor, Hawati (2009)
Beberapa kajian lepas mengenai integrasi kewangan mendapati pasaran saham ASEAN-5 berintegrasi di peringkat global dan regional.